Nb impurity-bound excitons as quantum emitters in monolayer WS2 - Leyi Loh; Yi Wei Ho; Fengyuan Xuan; Andrés Granados del Águila; Yuan Chen; See Yoong Wong; Jingda Zhang; Zhe Wang; Kenji Watanabe; Takashi Taniguchi; Paul J. Pigram; Michel Bosman; et al. (Nature Communications)
Abstract Point defects in crystalline solids behave as optically addressable individual quantum systems when present in sufficiently low concentrations. In two-dimensional (2D) semiconductors, such quantum defects hold potential as versatile single photon sources. Here, we report the synthesis and optical properties of Nb-doped monolayer WS2 in the dilute limit where the average spacing between individual dopants exceeds the optical diffraction limit, allowing the emission spectrum to be studied at the single-dopant level. We show that these individual dopants exhibit common features of quantum emitters, including narrow emission lines (with linewidths <1 meV), strong spatial confinement, and photon antibunching. These emitters consistently occur within a narrow spectral range across multiple samples, distinct from common quantum emitters in van der Waals (vdW) materials that show large ensemble broadening. Analysis of the Zeeman splitting reveals that they can be attributed to bound exciton complexes comprising dark excitons and negatively charged Nb.